PENDIDIKAN POLA HIDUP SEHAT MELALUI LITERASI KESEHATAN DI KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Rusmana, Agus (Dharmakarya, 2017)
The people of Lembang Sub-district get too much information about health due to the easy access to information sources that cause difficulties in identifying the right source of information. For that reason, there needs to be information literacy training that enables them to recognize needs, improve knowledge and ability to access resources, increase knowledge and ability to acquire, improve knowledge and evaluate ability, how to improve knowledge and ability of society in utilizing health information. The methods used in the training are lectures and training to recognize health characteristics with examples of cases of cataract disease. The result of this training is that participants gain an understanding of the literacy of health information, especially environmental health.